A inserção da perspectiva ciência-tecnologia-sociedade na formação inicial de professores de Química - München, Sinara (2016)
In this work it was investigated the insertion of the Science- Technology- Society perspective (STS) in the initial formation of teachers. The development happened in a curricular component of Teaching Practice, with students from a Bachelor Course in Chemistry from an Institution of the Central-West region of the country. The tools used for the data collection were two questionnaires and didactic sequences (DS) elaborated by undergraduates who were taking part of the research. From the data of the questionnaire, it is indicated that the students have an incipient knowledge about the STS approach in teaching, and according to the VOSTS questionnaire categorization, it is understood the STS interrelation according to the plausible category, what varies conforming the analysis dimension, because some aspects still reinforce simplistic view of Science and technology. The DS built were analyzed from an instrument elaborated by Silva and Marcondes (2015). In those, it is highlighted some aspects as the use of themes, the attempt of retrieving the social issue by the end of the DS, the discussion of controversial subjects and environmental problems, and the weaknesses highlighted are the exemplification, the approach distinctively conceptual and disciplinary and the absence of discussing technological issues. It is considered the insertion of the STS perspective in a component of teaching practice as viable and important in the formation of Chemistry teachers, because from the DS analysis it was possible to observe that this experience challenged the students to think on a teaching organization from another perspective. Although with some limitation, It is understood that it is necessary that teachers in formation have some places of discussion and reflection about the approaches with a wider character based on themes/issues related to context, and that can discuss the patterns of scientific and technological development.